Comparing the stock recommendation performance of investment banks and independent research firms - Barber, Brad M.; Lehavy, Reuven; Trueman, Brett (Journal of Financial Economics, 2007)
From January 1996 through June 2003, the average daily abnormal return to independent research firm buy recommendations exceeds that of investment bank buy recommendations by 3.1 basis points (almost 8 percentage points annualized). Investment bank buy recommendation underperformance is more pronounced following the NASDAQ market peak (March 10, 2000) and strikingly so for buy recommendations on firms that recently conducted equity offerings. In contrast, investment bank hold and sell recommendations outperform those of independent research firms by 1.8 basis points daily (412 percentage points annualized). These results suggest reluctance by investment banks to downgrade stocks whose prospects dimmed during the bear market of the early 2000s, as claimed in the SEC's Global Research Analyst Settlement.